2019
DOI: 10.1108/jpbm-12-2018-2164
|View full text |Cite
|
Sign up to set email alerts
|

The power of brand passion in sports apparel brands

Abstract: Purpose The purpose of this study is to determine if brand passion shapes attitudinal brand loyalty while driving a series of important brand-related outcomes (i.e. brand advocacy, social media following, sense of community, willingness to pay a premium price and alternative devaluation). These aspects are explored for sports apparel brands after considering the perceptions of Iranian consumers. Design/methodology/approach This study is based on the analysis of survey data gathered online and face-to-face fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 152 publications
(251 reference statements)
4
48
0
Order By: Relevance
“…The interest in the concept of passion has flourished in recent years among both marketing practitioners and academicians (Pourazad et al, 2019; Gilal et al, 2021). As such Vallerand et al (2003) have introduced a dualistic model of passion (e.g., harmonious and obsessive) for valued activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interest in the concept of passion has flourished in recent years among both marketing practitioners and academicians (Pourazad et al, 2019; Gilal et al, 2021). As such Vallerand et al (2003) have introduced a dualistic model of passion (e.g., harmonious and obsessive) for valued activities.…”
Section: Introductionmentioning
confidence: 99%
“…Both market research practitioners and academic marketing researchers have witnessed a growing interest in capturing customer brand passion (Pourazad et al, 2019). Therefore, research into a marketing realm has noted the importance of brand passion in strengthening positive word‐of‐mouth (Ahn, 2020; Herrando et al, 2017; Swimberghe et al, 2014), improving willingness‐to‐pay a price premium (Albert et al, 2013; Ghorbanzadeh et al, 2020), purchase intentions (Bauer et al, 2007), and brand evangelism (Swimberghe et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, researchers have shown that brands that develop and maintain deep emotional bonds with their consumers can enjoy high brand advocacy (Pourazad, Stocchi, & Pare, 2019) and active brand loyalty (Hemsley‐Brown & Alnawas, 2016), and that may boost willingness to pay a premium pricing (Albert et al, 2013) and positive word‐of‐mouth tendencies (Loureiro, Costa, & Panchapakesan, 2017; Loureiro, Sarmento, & Le Bellego, 2017). Despite increasing interest in brand passion, the exploration into antecedents is marginalized, and only a handful of studies have begun to examine predictors of brand passion.…”
Section: Introductionmentioning
confidence: 99%
“…Study results also show that brand passion has a positive influence on brand loyalty (β=0,683; p<0,001). Studies that Hemsley-Brown and Alnawas (2016), Pourazad et al, (2019) and Albert et al, (2013) carried out this finding. This study also reveals that brand passion mediates the relationship between hedonic value and brand loyalty (β=0,346; p=0,001).…”
mentioning
confidence: 56%
“…Study results revealed that brand passion has the most potent influence on brand loyalty compared to the other two components. Pourazad et al (2019) revealed in their study that brand passion had a positive influence on attitudinal brand loyalty to sportswear brands. Study results showed that the positive influence of brand passion on attitudinal brand loyalty was significant.…”
mentioning
confidence: 97%